Micronucleus frequency in exfoliated buccal cells from hairdresser who expose to hair products - Koh Hui Yee; Alma Linggar Jonarta; Regina TC. Tandelilin (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Hairdresser is one of the fastest growing occupations in today’s society. Hairdresser help styling, cutting, colouring, perming, curling, straightening hair and various treatment to customer. Somehow, hairdresser are constantly exposed to chemical substances such as aromatic amines, hydrogen peroxide, thioglycolic acid, formaldehyde in hair products which can cause damage to human’s genome. Micronucleus is one of the effective biomarker for processes associated with the induction of DNA damage. Purpose: The aim of this study was to determine the micronucleus frequencies in buccal mucosa epithelial cells of hairdresser who were exposed to chemical of hair products. Method: This study was conducted on twenty female subjects, who were divided into 2 groups: exposed and non-exposed (control) group. All subjects recruited were working in the same beauty salon. Buccal cells were obtained from each individual by using cytobrush. The cells were stained with modified Feulgen-Ronssenback method and counting of micronucleus per 1000 cell was done under light microscope. The data were analyzed using independent t-test and one-way Anova (p<0.05). Result: The result showed a significant difference in micronucleus frequency between 2 groups. There were a significantly increase of micronucleus frequency in hairdressers and increase of  micronucleus frequency with the longer duration of exposure. Conclusion: It concluded that the chemical substances of hair products had affected the micronucleus frequency ofthe epithelial cells in buccal mucosa of hairdressers.